The small GTPase RAB24 and vesicle trafficking from the endoplasmic reticulum to the Golgi apparatus - Antony, Anson (My University, 2025)
The small GTPase RAB24 is an unusual RAB protein, which is originally reported to localize in the endoplasmic reticulum (ER), cis-Golgi region and late endosomal structures. Several studies have shown that RAB24 is involved in autophagy, endocytosis and cell division, but its association to the cis-Golgi has not been studied. However, preliminary data from the host laboratory implied that RAB24 may play a role in ER-Golgi trafficking. Therefore, the aims of this thesis were to study the structural integrity and location of the Golgi complex in wild-type (WT) and RAB24-knockout (KO) hepatocyte cell lines, and to investigate the role of RAB24 in the ER-Golgi vesicle transport. The integrity of the Golgi ribbons was analyzed by culturing WT and RAB24-KO Huh7 cells at +37°C and +40°C, and staining the cells using an antibody against the Golgi marker GM130. A GFP-tagged, temperature-sensitive vesicular stomatitis virus glycoprotein (VSVG-ts045-eGFP) was used to conduct the ER-Golgi protein trafficking assay. At +40 °C, VSVG-ts045-eGFP protein cannot exit the ER due to misfolding. When the cells are shifted to +32 °C, the synchronized transport of the protein from the ER to the Golgi can be monitored. For the vesicle trafficking assay, cells expressing VSVG-ts045-eGFP were collected at different time points after shifting from +40 °C to +32 °C, and the colocalization of eGFP and the Golgi marker GM130 were analyzed using confocal microscopy. Further, deglycosylation assay was performed using endoglycosidase H (Endo H) enzyme that removes N-linked glycans from proteins that have not exited the ER. Western blotting was used to analyze the presence of VSVG-ts045-eGFP protein at the ER and post-ER compartments in WT and RAB24-KO cells at different time points after shifting the cells from +40°C to +32°C. At +37 °C, the Golgi ribbons were positioned on top of the nucleus in WT cells, whereas in the RAB24-KO cells, the Golgi ribbons localized around the nucleus. At +40 °C, the GM130-positive Golgi ribbons were fragmented in both WT and RAB24-KO cells, likely due to heat stress. Confocal microscopy revealed retarded ER-to-Golgi trafficking of VSVG-ts045-eGFP in RAB24-KO cells compared with the WT cells. However, no differences were observed in the Endo H sensitivity assay between the two cell lines. The results suggest that RAB24 may play a role in positioning of the Golgi apparatus in relation to the nucleus, and in ER-to-cis-Golgi trafficking.
Keywords: RAB24, Golgi, endoplasmic reticulum, vesicle trafficking, VSVG-ts045-eGFP, endoglycosidase H, deglycosylation, cancer